2012
DOI: 10.1159/000332391
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Maternal Uric Acid Concentration with Small-for-Gestational-Age Fetuses in Normotensive Pregnant Women

Abstract: Aim: Elevated maternal serum uric acid is associated with small-for-gestational-age (SGA) fetuses. We investigated whether uric acid concentrations in normotensive pregnant women are correlated with fetal growth and related to kidney function. Methods: We carried out a case-control study using 40 patients who delivered SGA fetuses identified from the perinatal database and 80 patients who delivered appropriate-for-gestational-age (AGA) fetuses as the controls at Okayama University Hospital. Blood pressure, ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
(28 reference statements)
7
30
0
Order By: Relevance
“…These findings are consistent with other studies conducted in different populations and durations of pregnancy; Laughon et al studied 212 normotensive pregnant women in Pittsburgh and reported that hyperuricemia during the second trimester or pregnancy was associated with a lower birth weight [23]. In another study of 120 Japanese normotensive pregnant women, Akahori et al documented that hyperuricemia in the third trimester of pregnancy is an independent risk factor for SGA delivery [4]. These results fulfill two important criteria in evaluating the causal relationship of associated factors: 1) consistency of the associations among studies conducted in different circumstances; and 2) the exposure occurred before the outcome.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings are consistent with other studies conducted in different populations and durations of pregnancy; Laughon et al studied 212 normotensive pregnant women in Pittsburgh and reported that hyperuricemia during the second trimester or pregnancy was associated with a lower birth weight [23]. In another study of 120 Japanese normotensive pregnant women, Akahori et al documented that hyperuricemia in the third trimester of pregnancy is an independent risk factor for SGA delivery [4]. These results fulfill two important criteria in evaluating the causal relationship of associated factors: 1) consistency of the associations among studies conducted in different circumstances; and 2) the exposure occurred before the outcome.…”
Section: Discussionsupporting
confidence: 88%
“…These associations have also been identified by other studies [4,14]. The association of excessive weight gain and impaired renal function with hyperuricemia can be explained by the overproduction and reduced renal excretion of uric acid, respectively [14].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Indirect measures of GFR in pregnancy, such as serum creatinine and uric acid, also support a positive relationship with birth weight [11][13]. Of the existing studies relevant to the GFR-fetal size relationship, none have quantitated it in straightforward physiologic terms such as grams per fetal weight per ml/min GFR.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study involving 1,487 cases, Joel R. [17] also confirmed Hawkins' conclusion, wherein he considered that the corrected UA according to gestational age can better predict adverse perinatal outcomes than random UA value, and its sensitivity and specificity were 93% and 27%, respectively. Through comparing the perinatal period information of women who have normal blood pressure, but respectively deliver small-for-gestational age infants and infants of right age, Akahori Y. et al [18] found that the levels of hematuria acid, creatinine and blood pressure of the former were obviously higher than those of the latter. Increased SUA is correlated to mild kidney function damage and LBW infants.…”
Section: Discussionmentioning
confidence: 99%